Evolution and comparison of food safety governance in China—based on DTM model - Wang, Jiayi; Fan, Xiaonan; Dai, Minghua (Frontiers in Sustainable Food Systems, 2025)
Scientific and effective food safety governance policies can regulate the activities of food producers and enhance consumers' confidence in food safety, which are the cornerstone of social harmony and stable development. The existing research has focused on the policy content, hot topics, and the application of policy tools, but has lacked the dynamic tracking of food safety governance policies and ignored the investigation of the causal mechanism between policy tools and governance effectiveness. Based on the Dynamic Topic Model (DTM), this research systematically examines the evolutionary pathways, phase-specific features of food safety governance policies in China, and the correlation mechanism with governance effectiveness as well. By collecting and analyzing 675 national policy documents from 1979 to 2024 in China, the policy evolution is divided into three main stages, including Experiential Regulation and Legalization Exploration Stage, Legal Restructuring and Institutional Strengthening Stage, and Smart Governance and Collaborative Co-governance Stage. The findings show that: (a) A total of 15 hot topics of food safety governance policies are identified, which include market supervision, production process regulation, national standards and food additives, inspection and testing technologies, and catering service safety, etc. (b) In terms of horizontal analysis, China's food safety governance policy has established a comprehensive governance framework by clarifying the responsibilities of various levels of institutions, strengthening full-chain supervision, setting up demonstration projects and special inspections, and implementing regular risk monitoring. (c) In the longitudinal analysis, the evolution of China's food safety governance policies has gradually shifted from single supervision, export orientation and accident response to multi-party governance, internal and external coordination and risk prevention, which reflects the continuous improvement of the legalization, coordination and intelligence of China's food safety governance policies. The evolution analysis of food safety governance policy topics is of great significance for optimizing the regulatory system, enhancing governance efficiency, and safeguarding public health.